2011
DOI: 10.1159/000327532
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Encapsulated Cells Overexpressing Alpha-<i>L</i>-Iduronidase Correct Enzyme Deficiency in Human Mucopolysaccharidosis Type I Cells

Abstract: Mucopolysaccharidosis I (MPS I) is an autosomal recessive lysosomal storage disease due to deficient α-L-iduronidase (IDUA) activity. It results in the accumulation of the glycosaminoglycans (GAGs) heparan and dermatan sulfate and leads to several clinical manifestations. Available treatments are limited in their efficacy to treat some aspects of the disease. Thus, new approaches have been studied for the treatment of MPS I. Here, we tested the ability of recombinant baby hamster kidney cells transfected with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Wild‐type littermates (WT, Idua −/+ and Idua +/+ ) and MPS I ( Idua −/− ) mice (donated by Elizabeth Neufeld, UCLA) with a C57BL/6 background were used in this study. Animals were genotyped at 21 days as previously described . Male and female WT and MPS I mice with two ( n = 4‐6), six ( n = 7‐12) and 8 months old ( n = 7‐6) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Wild‐type littermates (WT, Idua −/+ and Idua +/+ ) and MPS I ( Idua −/− ) mice (donated by Elizabeth Neufeld, UCLA) with a C57BL/6 background were used in this study. Animals were genotyped at 21 days as previously described . Male and female WT and MPS I mice with two ( n = 4‐6), six ( n = 7‐12) and 8 months old ( n = 7‐6) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Cytological analysis showed a marked reduction in GAG storage within MPS I cells (Baldo et al, 2011). Ongoing experiments are under way in the MPS I mouse model.…”
Section: Cell Microencapsulationmentioning
confidence: 86%
“…An interesting analysis would be to compare results at different times, plotting temporal changes in gene expression [21]. Studies have already shown the viability of encapsulated cells for longer culture periods, up to 45 days [30]. In order to improve the model, an increment in time culture could be carried out to asses if a longer period induces different expression of other markers.…”
Section: Discussionmentioning
confidence: 99%